(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The primary aim of this study is to analyze investors’ perception towards financial disclosure of Indian listed companies. A survey method was considered to collect responses from Stock Analysts, Brokers, Individual investors and Academics. The received responses were analyzed using descriptive tools such as mean and standard deviation; additionally, a rank was provided based on the mean score, and an F test was performed to determine the study’s significance level. The result of the study specified that investors’ perception was neither adequate nor relevant to investment decisions. The study presented various findings based on variables, and suggestions were also provided. In turn, it will be helpful in improving the efficiency of voluntary disclosure practices of the listed companies.